2005
DOI: 10.1093/pcp/pci069
|View full text |Cite
|
Sign up to set email alerts
|

Plant Cell Growth and Ion Flux Responses to the Streptomycete Phytotoxin Thaxtomin A: Calcium and Hydrogen Flux Patterns Revealed by the Non-invasive MIFE Technique

Abstract: Thaxtomin A, a key phytotoxin produced by plant pathogenic Streptomyces sp., is implicit in common scab disease expression in potato. Primary targets and modes of action of thaxtomin A toxicity in plant cells are not well understood. In this work, early signalling events associated with thaxtomin A toxicity were studied using the ion-selective microelectrode ion flux estimation (MIFE) technique. Thaxtomin A-induced changes in net ion fluxes were measured across the plasma membrane (PM) of root and pollen tube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 68 publications
0
53
0
10
Order By: Relevance
“…Results in Figure 2, B and C, indicate that with regard to the rapid senescence that occurs in detached leaves kept in the dark, application of Gd 3+ , a channel blocker that prevents inward currents through plasma membrane Ca 2+ -conducting channels (Tegg et al, 2005), mimics the phenotype shown by dnd1. Further studies were undertaken to determine if the effect of Gd 3+ on senescence programming could be observed at the biochemical and gene expression level.…”
Section: Resultsmentioning
confidence: 89%
“…Results in Figure 2, B and C, indicate that with regard to the rapid senescence that occurs in detached leaves kept in the dark, application of Gd 3+ , a channel blocker that prevents inward currents through plasma membrane Ca 2+ -conducting channels (Tegg et al, 2005), mimics the phenotype shown by dnd1. Further studies were undertaken to determine if the effect of Gd 3+ on senescence programming could be observed at the biochemical and gene expression level.…”
Section: Resultsmentioning
confidence: 89%
“…Auxin effects on the morphological development of len-ticels or periderm during early tuber growth, a period of susceptibility to infection by S. scabiei (2,4), might help explain how auxin treatments confer protection against common scab disease. Furthermore, recent evidence from our laboratory suggests an interaction whereby increased sensitivity to auxin correlates with an increased sensitivity to thaxtomin A (37).…”
mentioning
confidence: 79%
“…4A). Promotion of cytosolic Ca 2+ spikes in roots of Arabidopsis seedlings by application of several different ligands has been shown to inhibit primary root growth (26,32). In addition, we have found that some members of the CNGC protein family are expressed in roots, contribute to Ca 2+ uptake, and facilitate Ca 2+ -mediated inhibition of root elongation under some conditions (33).…”
Section: His-gchismentioning
confidence: 99%
“…S6A. Lanthanides such as Gd 3+ and La 3+ block plant plasma membrane Ca 2+ channels (26). Gd 3+ has been specifically shown to block inwardly rectified cyclic nucleotide-activated Ca 2+ channels in the plasma membrane of Arabidopsis leaf cells (20).…”
mentioning
confidence: 99%